Effect of renal impairment on the pharmacokinetics of bupropion and its metabolites - Turpeinen, Miia (Blackwell Science Inc, 2007)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT: There is an ongoing debate regarding the effect of renal impairment on CYP related metabolic activities. The possible effect of renal impairment on hepatic CYP2B6 activity, or on bupropion pharmacokinetics in renally impaired subjects without dialysis treatment has not yet been investigated. WHAT THIS STUDY ADDS: Bupropion clearance was found to be significantly decreased in patients with renal impairment. This study provides further evidence for interplay between the role of the kidney and liver in drug disposition, and opens novel lines of research with respect to the regulation of CYP2B6. AIMS: To investigate the effect of kidney disease on bupropion pharmacokinetics and on cytochrome P450 (CYP) 2B6 activity as measured by bupropion hydroxylation. METHODS: In an open parallel group study, 17 healthy, nonsmoking subjects and 10 patients with impaired kidney function received a single 150 mg oral dose of sustained release bupropion. Plasma concentrations of bupropion and its metabolites were measured for up to 72 h. Subjects were genotyped for the CYP2B6 SNPs 1459 C>T, 785 A>G and 516 G>T. RESULTS: Bupropion AUC was 126% higher (P< 0.0001, 95% CI +72%, +180%), C(max) 86% higher (P = 0.001, 95% CI +40%, +131%), CL/F 63% lower (P = 0.001, 95% CI −29%, −96%), and t(1/2) 140% longer (P = 0.001, 95% CI +76%, +204%) in renally impaired patients. However, only minor changes were detected in the concentrations of the metabolites. In renally impaired subjects the hydroxybupropion : bupropion AUC ratio was decreased by 66% (P = < 0.0001, 95% CI −19%, −114%) and the hydrobupropion : bupropion AUC ratio by 69% (P = 0.001, 95% CI +8%, −146%) compared with controls. CONCLUSIONS: The CL/F of bupropion was significantly lower in subjects with renal impairment. Because the principal metabolites of bupropion possess similar pharmacological activity to the parent compound, dosage recommendations for patients with renal impairment cannot be given. A direct effect of renal impairment on CYP2B6 activity could not be demonstrated by the present study design.